1999
DOI: 10.1136/bjsm.33.6.387
|View full text |Cite
|
Sign up to set email alerts
|

Heart dimensions may influence the occurrence of the heart rate deflection point in highly trained cyclists.

Abstract: Objectives-To determine whether the heart rate (HR) response to exercise in 21 highly trained cyclists (mean (SD) age 25 (3) years) was related to their heart dimensions. Conclusions-The HR response is curvilinear during incremental exercise in a considerable number of highly trained endurance athletes-that is, top level cyclists. The departure of HR increase from linearity may predominantly occur in athletes with thicker heart walls. (Br J Sports Med 1999;33:387-392) Methods-Before

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
(35 reference statements)
2
21
0
2
Order By: Relevance
“…Each of 3 tests were performed on a cycle ergometer (Ergometrics 900; Ergo-line; Barcelona, Spain) following a ramp protocol until exhaustion. This type of protocol has been used for the physiological evaluation of professional cyclists in several previous studies [13][14][15][16][17][18]. Starting at 0 W, the workload was increased by 25 W · min Ϫ1 and pedaling cadence was maintained from 70 to 90 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of 3 tests were performed on a cycle ergometer (Ergometrics 900; Ergo-line; Barcelona, Spain) following a ramp protocol until exhaustion. This type of protocol has been used for the physiological evaluation of professional cyclists in several previous studies [13][14][15][16][17][18]. Starting at 0 W, the workload was increased by 25 W · min Ϫ1 and pedaling cadence was maintained from 70 to 90 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Prabhu et al [50], however, found no change in VT, f b , or TI/TTOT with varying pedaling rates from 40 to 80 rpm. In the present investigation, we have followed the methodology of previous studies with professional cyclists [13][14][15][16][17][18], in which subjects were allowed to choose their preferred cadence within the range of 70 to 90 rpm. This can better simulate actual cycling conditions compared with tests at a fixed cadence.…”
mentioning
confidence: 99%
“…Several investigators report that the HR d only occurs in certain subjects, and if detected, does not necessarily coincide with the AT [6][7][8]. In a recent report from our laboratory, we found the existence of HR d in the majority of a group of professional road cyclists (ϳ70% of a total of 21 subjects) [9].…”
mentioning
confidence: 96%
“…In addition, despite the long duration of cycling events such as 3-week stage races, the relative contribution of intense exercise is surprisingly high during the more physically taxing events (mountain passes, time trials, sprints, "breakaways" etc.) [1].Several investigators have analyzed a number of physiological variables in professional cyclists, both in laboratory [2][3][4][5][6][7] and field settings [1,[8][9][10]. However, no prospective, long-term investigation has established the specific physiological adaptations which occur in professional cyclists as a response to training and competition during a typical sports season (generally including different periods in terms of training volume and/or intensity; i.e., precompetition or training, competition, and postcompetition or "active" rest periods).…”
mentioning
confidence: 99%